2015
DOI: 10.1080/12460125.2015.1046681
|View full text |Cite
|
Sign up to set email alerts
|

Annotation management: a Group decision support system for nurses tasks

Abstract: International audienceWe develop a 5-year empirical investigation that is giving us broad and deep insights to characterise activity management in the palliative ward of an oncology hospital, and offer effective support for group decision-making and collaborative activity of caregivers. Following this observation period, we propose a software prototype based upon annotations in which dealing with patients’ state and evolution is a complex organisational task. We based our conception of an annotation tool on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Indeed such tools may not be used by everyone, and may exclude some parts of the population that may be particularly important to consider for studying social inequalities in health, or not used in the same manner which can have an impact on their completeness. Sociological studies that followed the implementation of informatics tools for health professionals showed that entire sections of the information needed for care continued to circulate in written form ( 13 ). Such “dark data” ( 12 ) will not be available in an analysis labeled as Big Data showing that the advent of Big Data approaches does not solve the problem of data representativeness and completeness, bias, measurement error.…”
Section: Big Data In Health: Some Key Scientific Issuesmentioning
confidence: 99%
“…Indeed such tools may not be used by everyone, and may exclude some parts of the population that may be particularly important to consider for studying social inequalities in health, or not used in the same manner which can have an impact on their completeness. Sociological studies that followed the implementation of informatics tools for health professionals showed that entire sections of the information needed for care continued to circulate in written form ( 13 ). Such “dark data” ( 12 ) will not be available in an analysis labeled as Big Data showing that the advent of Big Data approaches does not solve the problem of data representativeness and completeness, bias, measurement error.…”
Section: Big Data In Health: Some Key Scientific Issuesmentioning
confidence: 99%